Humanitarian Policy and Information Security as Main Aspects Counteractions Spreading War Russia Against Ukraine - Туренко, Віталій Едуардович; Перепелиця, Наталія Олегівна (Київський національний університет імені Тараса Шевченка, 2024)
The article explores the specific and foundational aspects of humanitarian policy as a crucial element in countering the information warfare conducted by the Russian Federation against Ukraine. Several key considerations in this effort include: 1. Promotion of humanitarian values: аdvocating and supporting humanitarian values such as tolerance, equality, and respect for human rights play a proactive role for the state; 2. Development of educational and cultural initiatives: implementing programs that foster understanding and mutual appreciation among diverse cultures and nationalities is essential. 3. Safeguarding citizens’ rights and freedoms: authorities should take responsibility for protecting fundamental rights and freedoms, including freedom of speech, the right to information, and privacy; 4. Enhancement of media literacy: initiatives aimed at improving media literacy among the population are crucial. individuals with heightened media literacy are less susceptible to manipulation. 5. International collaboration and diplomacy: collaborative efforts and diplomatic endeavors are necessary for exchanging best practices in humanitarian policy and countering information aggression. 6. Provision of humanitarian assistance: offering humanitarian aid and support to those affected by information aggression is vital. The importance of safeguarding both state and personal information cannot be overstated, particularly in light of the increasing prevalence of electronic systems for governance and information exchange, especially amidst the full-scale war Russia is waging against Ukraine. There is an urgent need to bolster measures that ensure the confidentiality and integrity of data to prevent the compromise of sensitive information and maintain trust and efficiency in administrative processes. Furthermore, economic security is a critical concern, as Ukraine’s economic wellbeing relies on defending against cyber threats. Successful cyber attacks can result in data breaches, financial losses, and a decrease in investor confidence, posing a significant risk to economic growth and stability. Therefore, robust information security measures are indispensable for sustaining Ukraine’s economic prosperity.

У статті досліджуються засадничі аспекти гуманітарної політики як одного з ключових елементів протидії інформаційній війні, що ведеться Російською Федерацією проти України. Кілька ключових міркувань у цій сфері: 1. Просування гуманітарних цінностей: просування та підтримка гуманітарних цінностей, таких як толерантність, рівність та повага до прав людини, відіграє проактивну роль для держави; 2. Розвиток освітніх та культурних ініціатив: реалізація програм, які сприяють взаєморозумінню та взаємоповазі між різними культурами та національностями, має важливе значення. 3. Забезпечення прав і свобод громадян: влада має взяти на себе відповідальність за захист фундаментальних прав і свобод, зокрема свободи слова, права на інформацію та приватність; 4. Підвищення медіаграмотності: ініціативи, спрямовані на підвищення медіаграмотності населення, мають вирішальне значення. люди з підвищеною медіаграмотністю менш схильні до маніпуляцій. 5. Міжнародна співпраця та дипломатія: спільні зусилля та дипломатичні зусилля необхідні для обміну кращими практиками в гуманітарній політиці та протидії інформаційній агресії. 6. Надання гуманітарної допомоги: надання гуманітарної допомоги та підтримки тим, хто постраждав від інформаційної агресії, є життєво важливим. Важливість захисту як державної, так і особистої інформації неможливо переоцінити, особливо у світлі все більшого поширення електронних систем управління та обміну інформацією, особливо в умовах повномасштабної війни, яку Росія веде проти України. Доведена нагальна потреба в посиленні заходів, які забезпечують конфіденційність і цілісність даних, щоб запобігти компрометації чутливої інформації та зберегти довіру й ефективність адміністративних процесів. Крім того, економічна безпека є критично важливим питанням, оскільки економічний добробут України залежить від захисту від кіберзагроз. Успішні кібератаки можуть призвести до витоку даних, фінансових втрат і зниження довіри інвесторів, що становить значний ризик для економічного зростання та стабільності. Тому надійні заходи інформаційної безпеки є необхідними для підтримки економічного процвітання та національної безпеки України.
Гуманітарна політика та інформаційна безпека як основні аспекти протидії поширенню війни Росії проти України
Keywords: humanitarian policy; information security; Russia’s full-scale war against Ukraine; international cooperation; information warfare; post-truth; cyber security; fakes; educational and cultural practices; гуманітарна політика; інформаційна безпека; повномасштабна війна Росії проти України; міжнародна співпраця; інформаційна війна; постправда; кібербезпека; фейки; освітні та культурні практики